Analisis Push And Pull Motivation Factors Terhadap Minat Berkunjung Wisatawan Ke Kabupaten Karangasem, Bali - Desak Made Febri Purnama Sari; Safitri, Ni Komang; Widiantari, Komang Sri; Wita Indrayani, I Gusti Ayu Putu (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
Research purposes to identify the factors influencing tourists' interest in visiting Karangasem Regency, Bali. A quantitative data analysis was conducted involving 192 domestic tourists visiting Karangasem Regency. The data were analyzed using Confirmatory Factor Analysis (CFA) in SPSS version 25. The analysis revealed that from the initial 32 indicators tested, three main factors emerged that can explain the interest in visiting Karangasem Regency: